Identification of Internal Parasites in Sheep and Goats in Garmiyan Province/Kurdistan Region/Iraq - AL-Zandee, Mohammed T.; Essa, Hiwa Y.; Jabary, Osman M.; AL-Shateri, Aram A.; AL-Bajalan, Yousef KH. (Sulaimani Journal for Pure and Applied Sciences, 2016)
A study was conducted to identify different kinds of internal parasites that are distributed in ruminants in Garmiyan province, southeast Kurdistan region/ Iraq. Fecal samples from 460 animals (360 sheep and 100 goats) were examined from April to December, 2015 that includedapplying different parasitological techniques. Mini-flotac flotation method was used for the detection of nematode and cestode helminths; the sedimentation technique used for trematodes whereas for recovering lung worms and infective larvae Baermann technique was applied andculturing of fecal samples was implemented for the differentiation of free living stages. The study revealed that overall 46.52% of tested animals had been infected with several gastrointestinal helminths that were distributed between 48.05% in sheep and 41% in goats respectively. Marshallagia marshalli was by far the most prevalent parasite in the area with about 74% of positive samples followed by Nematodes like eggs including (Trichostrongylus spp., Teledorsagia circumcincta, Haemonchus contortusand Cooperia spp.) then lung worms. The majority of samples were mixed infection by nearly 76% and the rest were single infection. According to the age category, adult animals recorded more rates of infection (49.09%) than young (39.84%),while in regards tothe sex factor; females were relatively more than males (47.13% compared to 42.37%). The study suggested that susceptibility of animals, environmental conditions in addition to managing trials implemented like husbandry and density of stocking may play a role in increasing contamination on pasture and increasing abundance of parasites. Other aspects like testing anthelmintic resistance and existing control measures used by people in this area should be taken into account when research is undertaken in the future.
Keywords: Gastrointestinal helminths GIHEgg per grame pg Miniflotac